The hive - Lyga, Barry; Jacobson, Tom; Beals, Jennifer; Baden, Morgan (2019)
It's the near future -- the day after tomorrow -- and the government has shut down online bullying once and for all. With BLINQ, its new social media platform, users can "like" or "share," but they can also "condemn" posts -- and if condemns reach a certain level, users can exact punishment from the original poster in real life. No more anonymous trolling! Instead... hive justice
Based on a story proposal by Jennifer Beals and Tom Jacobson
Keywords: Online social networks -- Juvenile fiction; Social media -- Juvenile fiction; Mobs -- Juvenile fiction; Vigilantes -- Juvenile fiction; Life change events -- Juvenile fiction; Grief -- Juvenile fiction; Fathers -- Death -- Juvenile fiction; Hackers -- Juvenile fiction; Conspiracies -- Juvenile fiction; Fugitives from justice -- Juvenile fiction; Young adult fiction; Dystopian fiction